Passive control of wake flow behind a square cylinder using a flat plate - Abbasi, Waqas Sarwar; Ismail, Saba; Nadeem, Sumaira; Rahman, Hamid; Majeed, Afraz Hussain; Khan, Ilyas; Mohamed, Abdullah (Frontiers in Physics, 2023)
In this study, the lattice Boltzmann method is used to control the wake flow of a single square cylinder using a flat plate attached at rear side of the cylinder. The Reynolds number (Re) is fixed at 150 and length of the plate is varied from 0.1 to 8.5. Three distinct flow modes are found in this study: unsteady, transient and steady flow over the range of plate length (L) ranging from 0.1 ≤ L ≤ 6.5, 6.75 ≤ L ≤ 7.5, and 7.75 ≤ L ≤ 8.5, respectively. The vorticity is found to exhibit different flow structures named as hair pin like structure, ellipse like structure and elongated bubbles like structure. A complete wake control is achieved beyond plate length 7.75. This study reveals that the drag and lift coefficients exhibit unsteadiness at small plate lengths in lesser time steps, but as plate length increased, the unsteadiness slowed down and eventually disappeared confirming the steady flow pattern. The mean drag coefficient (CD_m), Strouhal number (St), root mean square value of drag and lift coefficients (CD_rms and CL_rms) reduce up to a maximum of 23.5%, 100%, 84.6% and 99.5%, respectively, due to presence of plate.